Model Desain Kurikulum Pewartaan Injil untuk Anak Usia Dini di Sekolah Minggu Rumah - Karnawati Karnawati; Ayin Claudia (Sekolah Tinggi Teologi Jaffray Jakarta, 2021)
Preaching of the gospel through Sunday schools for early childhood in schools is hampered by the pandemic situation. Therefore, it is necessary to design evangelism curriculum for these children while studying Sunday school at home. The purpose of this study is to propose a curriculum design model for evangelism to early childhood at home Sunday school. This research uses literature study method with descriptive qualitative approach. The result of this research is a curriculum design for evangelism that includes aspects of the objectives, content, curriculum organization, curriculum implementation, and evaluation. These aspects are explained in a simple example so that implementation is easy. This is also related to the readiness of parents in economic aspects, time and skills in teaching, as well as their understanding of the Bible. The contribution of this research is a contribution in the field of the Sunday school curriculum.